A REVIEW ON PROBLEM-SOLVING SKILLS OF CANDIDATE MUSIC TEACHERS ACCORDING TO THE VARIOUS VARIABLES: Example of Karadeniz Technical University - Yalçın YILDIZ (Fırat University, 2019)
In this study, candidate music teachers’ -studying in Karadeniz Technical University- problem-solving skills were tried to be examined. It is known that in